Implementasi Sistem Pengelolaan Manajemen Keuangan pada Tadika Tinta Khalifah Al Fikh Orchard Penang Malaysia - Siti Sa’baini; Syahrul Amsari (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Financial management is carried out to manage financial management activities based on the situation of data collection carried out at Tadika Tinta Khalifah Penang Malaysia, The aim of this research is to find out the management at Tadika Tinta Khalifah, namely budget planning, accounting and auditing. The research method uses qualitative research. The respondents in this research are the owner of Tadika Tinta Khalifah Penang Malaysia and the finance staff. Data collection methods include interviews. Financial management will be implemented based on needs and other costs, this requires cooperation so that financial management can run smoothly, the financial management of the ssilamic caliphate which is engaged in non profit activities is carried out through management where the previous intitution carries out initial planning, directng,implementation, financial managemen and news at any time. The aim is to improve quality and performance in general